Instrumen evaluasi kinerja preceptor dengan kepuasan, kepercayaan diri dan critical thinking preceptee dalam melaksanakan praktik klinik; pilot study - Maria Jeinny Regar; Syahrul Syahrul; Takdir Tahir (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
AbstractBackground: A preceptee require a qualified Preceptor to guide them in clinical teaching and learning activities to be more confident, satisfied with the guidance obtained and can improve their critical thinking skills in nursing action. For that we need terstandart instruments to measure it. The purpose of this pilot study was to determine the value of Cronbach's alpha instruments and understanding the structure of words contained in the instrument. Methods: a pilot study of the instrument Preceptor performance, satisfaction, confidence and critical thinking preceptee at 20 nursing students were obeying program nurses in hospitals Makassar. Results: The results obtained pilot study Cronbach's alpha values> 0.90, which indicates that the Internal Consistency good reliability, value corrected item-total correlation of each item> 0.90, which indicates that the item total correlation coefficients were very good and had a good word structure. Conclusion: Instrument performance Preceptor, Satisfaction, Confidence and Critical Thinking preceptee have internal structure of words and good consistency.